Heizmannia rajagopalani n. sp. (Diptera: Culicidae) in Kerala, India, a species previously misidentified as Hz. metallica (Leicester) - Natarajan, R.; Eapen, Alex; Jambulingam, P. (Zootaxa, 2020)
The original description of Heizmannia (Heizmannia) metallica (Leicester) from Malaysia, and specimens collected in India that were provisionally identified as Hz. metallica, were re-examined for their taxonomic status. Heizmannia metallica from Malaysia was found by Mattingly (1970) to be a junior synonym of Hz. indica (Theobald), whereas we found the specimens identified as Hz. metallica from India to differ distinctly from the holotype of Hz. metallica. We collected adults near Malabar Coast, Western Ghats which corresponded with Indian Hz. metallica sensu auctorum and here describe the previously misidentified species as Hz. (Hez.) rajagopalani n. sp. The adult male and female of the new species, and their genitalia, are described and illustrated.